COVID-19 Vaccines: Fabrication Techniques and Current Status - Mahajan, Ayushi; Kaur, Lakhvir; Singh, Gurjeet; Dhawan, Ravi K.; Singh, Lovepreet; Kaur, Anureet (Coronaviruses, 2022)
The year 2020 was the most challenging period due to the havoc caused by the outbreak of novel coronavirus SARS-CoV-2. Scientists and researchers all around the world have endeavored every possible approach to find solutions in context to therapeutics and vaccines to control the spread of this life-threatening virus. The acceleration instigated by the outbreak of SARS-CoV-2 and its mutated strains has leveraged the use of numerous platform technologies for the development of vaccines against this unfathomable disease. Vaccines could play an important role in mitigating the effects of COVID-19 and reducing the ongoing health crisis. Various innovative platforms like proteins, nucleic acids, viruses, and viral vectors have been exploited to fabricate vaccines depicting almost 90% of efficacy like BNT162b2, AZD1222, Ad5-nCoV, etc. Some of these vaccines are multipotent and have shown potent activity against newly emerged malicious strains of SARS-CoV-2 like B.1.351 and B.1.1.7. In this review article, we have gathered key findings from various sources of recently popularized vaccine candidates, which will provide an overview of potential vaccine candidates against this virus and will help the researchers to investigate possible ways to annihilate this menace and design new moieties.
Keywords: SARS-CoV-2